2014
DOI: 10.1080/19440049.2014.939720
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the exposure parameters that maximise the concentrations of the anaesthetic/sedative eugenol in rainbow trout (Oncorhynchus mykiss) skin-on fillet tissue

Abstract: Studies were conducted to determine the anaesthetic/sedative concentrations and durations that would maximise anaesthetic/sedative residue concentrations in rainbow trout (Oncorhynchus mykiss) skin-on fillet tissue. Rainbow trout (167-404 g) were exposed to 50 mg l(-1) AQUI-S(®) 20E (10% active ingredient, eugenol) in 17°C freshwater for durations up to 1440 min, 100 and 250 mg l(-1) AQUI-S(®) 20E for durations up to 240 min, and 500 and 1000 mg l(-1) AQUI-S(®) 20E for durations up to 90 min. Fish exposed to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…For example, Meinertz et al. () conducted a study in which Rainbow Trout were exposed to 5, 10, 25, 50, or 100 mg/L eugenol for extended periods of time to assess the effect of exposure dose on tissue residue levels and reported the highest residues in lightly sedated fish (i.e., no loss of equilibrium, little or no net avoidance) exposed to 5 mg/L for up to 24 h. Interestingly, fish exposed to 10 mg/L eugenol in this study were considered moderately sedated (i.e., near complete loss of equilibrium and moderate opercular movement), and higher eugenol concentrations resulted in deep sedation (i.e., complete loss of equilibrium and minimal or no opercular movement). In the course of a standard LC50 study involving Rainbow Trout exposed to clove oil (85–90% eugenol), Keene et al.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, Meinertz et al. () conducted a study in which Rainbow Trout were exposed to 5, 10, 25, 50, or 100 mg/L eugenol for extended periods of time to assess the effect of exposure dose on tissue residue levels and reported the highest residues in lightly sedated fish (i.e., no loss of equilibrium, little or no net avoidance) exposed to 5 mg/L for up to 24 h. Interestingly, fish exposed to 10 mg/L eugenol in this study were considered moderately sedated (i.e., near complete loss of equilibrium and moderate opercular movement), and higher eugenol concentrations resulted in deep sedation (i.e., complete loss of equilibrium and minimal or no opercular movement). In the course of a standard LC50 study involving Rainbow Trout exposed to clove oil (85–90% eugenol), Keene et al.…”
Section: Discussionmentioning
confidence: 84%
“…Others studies involving prolonged exposure to low concentrations of eugenol have been conducted, albeit with different objectives in mind. For example, Meinertz et al (2014) conducted a study in which Rainbow Trout were exposed to 5, 10, 25, 50, or 100 mg/L eugenol for extended periods of time to assess the effect of exposure dose on tissue residue levels and reported the highest residues in lightly sedated fish (i.e., no loss of equilibrium, little or no net avoidance) exposed to 5 mg/L for up to 24 h. Interestingly, fish exposed to 10 mg/L eugenol in this study were considered moderately sedated (i.e., near complete loss of equilibrium and moderate opercular movement), and higher eugenol concentrations resulted in deep sedation (i.e., complete loss of equilibrium and minimal or no opercular movement). In the course of a standard LC50 study involving Rainbow Trout exposed to clove oil (85-90% eugenol), Keene et al (1998) observed a slight loss of reactivity to fright stimuli among fish exposed to 1 mg/L, complete loss of reactivity to fright stimuli among fish exposed to 2 mg/L, and complete loss of reactivity to fright stimuli and partial loss of equilibrium among fish exposed to 5 mg/L eugenol.…”
Section: Discussionmentioning
confidence: 99%
“…However, soxhlet extraction usually takes several hours. Meinertz et al have done some excellent work relating to eugenol, and have developed a SPE method to determine the eugenol exposure conditions that maximize the concentration of eugenol in rainbow-trout skin-on fillet tissue [14,15]. However, the conditions of SPE still need to be studied in detail.…”
Section: Introductionmentioning
confidence: 96%
“…The previous reported methods for determining eugenol in animal tissues, include gas chromatography mass spectrometry combined with Soxhlet extraction procedure in silver perch fillet (Kildea, Allan, & Kearney, ), liquid chromatography–quadrupole ion–trap mass spectrometry connected with liquid–liquid extraction (LLE) procedure in rainbow trout plasma (Guénette, Hélie, Beaudry, & Vachon, ; Guénette, Ross, Marier, Beaudry, & Vachon, ; Guénette, Uhland, Hélie, Beaudry, & Vachon, ) and rat plasma (Beaudry, Guénette, & Vachon, ), liquid chromatography connected to a phenyl SPE clean‐up procedure in rainbow trout skin‐on fillet tissue (Meinertz, Porcher, Smerud, & Gaikowski, ), gas chromatography tandem triple‐quadrupole mass spectrometry combined with a C 18 SPE clean‐up procedure in fish and shrimp muscle (Li et al, ; Li et al, ; Li, Zhang, & Liu, ), and liquid chromatography–tandem mass spectrometry and dispersive solid‐phase extraction in shrimp, crab and carp muscle (Sun, Gao, & Lian, ). These methods focused on the determination of eugenol in two matrices, and the sample preparation procedures of the aforementioned methods are complicated and time‐consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Isotope dilution combined with mass spectrometry has been recognized as a primary method to establish a traceable and highly accurate method for the measurement of the amount of substances, because it is the preferred approach to reducing matrix interference from labeled analogs for each target analyte (Du, Perez‐Hurtado, Brooks, & Chambliss, ; Teo, Wong, Liu, Teo, & Lee, ). The isotopically labeled eugenol (eugenol‐d 3 ) shown in Figure as internal standard (IS) is a better choice for accurate quantification, and it was not used in the previous published papers for eugenol analysis in fish (Guénette et al, , , ; Kildea et al, ; Li et al, ; Meinertz et al, ). gas chromatography–ion trap tandem mass spectrometry (GC‐IT‐MS/MS) is sensitive, very selective and low‐cost instrument.…”
Section: Introductionmentioning
confidence: 99%